Carbon Paste Electrode Modified with Polystirenedivinylbenzene-a-Nitroso-B-Naphthol for Voltammetric Analysis of Pb(II) ion - RUSSULAREWATI (NIM 10505045), NURFITRI
Polystyrene divinylbenzene (PSDVB) is a porous polymer resin, and has a large surface area so that it can act as an adsorbent. This resin can be functionalized with bidentate ligand such as a-nitroso-B-naphthol (NN) to increase the number of the ligature and stabilize the fastening with the metal ion. Therefore in this research, chelating resin PSDVB-NN was used as modifier compound in the carbon paste working electrode to analyze Pb(II) with square wave stripping anodic voltametry. With the presence of chelating resin, it was expected to increase the effectiveness of Pb(II) deposition on the surface of the electrode. In this research, the complex formation between Pb(II) with the ligand did not occur. The advantages of modified carbon paste electrode can be seen in the measurement of Pb(II) at low concentration, i.e. 0,01-0,1 ppm. The optimum composition of PSDVB-NN in the working electrode was 3%. The optimum pH of buffer acetate used as media analysis was 4,5. Percent recovery of Pb(II) ranged between 96.38%-101.32% in the concentration range of 0,01-0,1 ppm and 1-10 ppm with correlation coefficient (R2) 0,9880-0,9986. Detection limit of carbon paste electrode with and without modification PSDVB-NN is 5.67 ppb and 8.73 ppb respectively.